Pengaruh Pelatihan Kerja Dan Beban Kerja Terhadap Prestasi Kerja Pegawai Pada Kantor Kelurahan Di Kecamatan Cipedes Kota Tasikmalaya - Ahilla Kamilatul Adlha; Kusuma Agdhi Rahwana; Gian Riksa Wibawa (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to determine the effect of job training and workload on employee performance at the Village Office in Cipedes District, Tasikmalaya City. This study uses a quantitative method of descriptive analysis method. The type of data used is primary data and secondary data, with a sample of 44 respondents from Kelurahan Office employees in Cipedes District, Tasikmalaya City, and using the saturated sample method. The data analysis tool used in this study was SPSS Version 25. Data collection techniques used literature studies, interviews, and questionnaires. The results of the study show that job training and workload simultaneously have a significant effect on employee performance. Job Training partially has a significant effect on Employee Performance. Workload partially has a significant effect on Employee Performance.